Atypical spindle cell lipomatous tumour presenting as a large retroperitoneal mass – a case report and review of the literature - Krupinska, Martyna; León, Carmen; López Henríquez, Rocío; Vázquez, Beatriz Esquivel; Rodríguez, Rosa Nieves Rodríguez; Marrero, Patricia Marrero; Plasencia, Luciano Delgado; Salido, Eduardo (Polish Journal of Pathology, 2022)
Atypical spindle cell lipomatous tumour (ASCLT) is a benign neoplasm that presents a variable proportion of atypical spindle and adipocytic cells, frequently expressing CD34, and embedded in myxoid or collagenous matrix. An important feature is a constant lack of either MDM2 or CDK4 amplification. It typically arises in the extremities. The retroperitoneum is a rare site of involvement. We report a case of a retroperitoneal ASCLT in a 62-year-old male. A differential diagnosis of ASCLT from the other mesenchymal, spindle-cell, and lipomatous tumours is crucial for optimal treatment and significantly influences the prognosis. A diagnosis should be warranted by the immunohistochemistry and molecular findings.